How the Way a Naphthalimide Unit is Implemented Affects the Photophysical and -catalytic Properties of Cu(I) Photosensitizers - Yang, Yingya; Doettinger, Florian; Kleeberg, Christian; Frey, Wolfgang; Karnahl, Michael; Tschierlei, Stefanie (Frontiers in Chemistry, 2022)
Driven by the great potential of solar energy conversion this study comprises the evaluation and comparison of two different design approaches for the improvement of copper based photosensitizers. In particular, the distinction between the effects of a covalently linked and a directly fused naphthalimide unit was assessed. For this purpose, the two heteroleptic Cu(I) complexes CuNIphen (NIphen = 5-(1,8-naphthalimide)-1,10-phenanthroline) and Cubiipo (biipo = 16H-benzo-[4′,5′]-isoquinolino-[2′,1′,:1,2]-imidazo-[4,5-f ]-[1,10]-phenanthrolin-16-one) were prepared and compared with the novel unsubstituted reference compound Cuphen (phen = 1,10-phenanthroline). Beside a comprehensive structural characterization, including two-dimensional nuclear magnetic resonance spectroscopy and X-ray analysis, a combination of electrochemistry, steady-state and time-resolved spectroscopy was used to determine the electrochemical and photophysical properties in detail. The nature of the excited states was further examined by (time-dependent) density functional theory (TD-DFT) calculations. It was found that CuNIphen exhibits a greatly enhanced absorption in the visible and a strong dependency of the excited state lifetimes on the chosen solvent. For example, the lifetime of CuNIphen extends from 0.37 µs in CH2Cl2 to 19.24 µs in MeCN, while it decreases from 128.39 µs to 2.6 µs in Cubiipo. Furthermore, CuNIphen has an exceptional photostability, allowing for an efficient and repetitive production of singlet oxygen with quantum yields of about 32 %.